Omnichannel Integration, Service Convenience, Personalization, And Price Transparency: Influences On Customer Satisfaction - Yeremia Wijayanto (Yayasan Riset dan Pengembangan Intelektual, 2026)
Against the backdrop of rapidly evolving retail environments where physical and digital channels converge, this study investigates the combined effects of omnichannel integration, service convenience, personalization, and price transparency on customer satisfaction. Drawing on the Stimulus-Organism-Response (S-O-R) framework and Expectation-Disconfirmation Theory, the research addresses critical gaps in existing literature by examining these four antecedent factors within a unified model, particularly in the understudied context of emerging markets. A quantitative research design employing Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze data from 150 omnichannel retail consumers in Indonesia. The results reveal that omnichannel integration (β = 0.312, p < 0.001), personalization (β = 0.245, p < 0.001), and price transparency (β = 0.189, p < 0.01) exert significant positive effects on customer satisfaction, with service convenience showing a marginally smaller but still meaningful impact (β = 0.167, p < 0.01). Together, these factors explain 62.3% of the variance in satisfaction. The findings contribute to retailing theory by validating the relative importance of channel integration versus customer-centric attributes, while offering strategic guidance for retailers seeking to design cohesive omnichannel experiences that foster long-term customer relationships.